Microcrystalline glass and preparation method thereof, tgv substrate and manufacturing method and application thereof
Patent Information
- Application Number
- CN202611208637.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-09
AI Technical Summary
[0004]当前行业一般采用硼硅玻璃和石英玻璃作为TGV基板的玻璃原材,石英玻璃由于其超高的成本及与芯片材质不匹配的超低热膨胀系数,使得其在芯片领域的封装难以拓展
[0034]本申请提供了一种微晶玻璃及其制备方法、TGV基板及其制造方法与应用,以质量百分比计,所述微晶玻璃包括:SiO2:69wt%~75wt%,Al2O3:5wt%~9wt%,P2O5:1wt%~3wt%,ZrO2:4wt%~7wt%,Na2O+K2O:0wt%~2wt%,Li2O:9wt%~13wt%,CaO:0.3wt%~1.3wt%,B2O3:0wt%~2wt%,且SiO2+Al2O3≥75wt%,0.12≤Li2O/SiO2≤0.18,1.25≤Li2O/Al2O3≤2。采用氧化物组成和含量在本申请范围内的微晶玻璃,并调控Li2O/SiO2、Li2O/Al2O3的值在本申请范围内,能够在微晶玻璃内部析出目标晶体二硅酸锂和透锂长石,使微晶玻璃内部晶体呈棒状交错,有利于抵抗TGV工艺中的裂纹产生和扩展;能够使微晶玻璃具备良好的机械强度,有利于抵抗TGV后制程工艺中的翘曲变形等情况;同时,本申请微晶玻璃具备良好的介电性能,还具备较高的透过率,可满足光学领域TGV工艺的需求;为TGV工艺提供机械性能优异的玻璃原材,可实现高密度通孔、盲孔、盲槽,通孔可实现高垂直度,通孔腰径比可达0.85。
Smart Images

Figure CN122878035A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of glass technology, and in particular to a microcrystalline glass and its preparation method, a TGV substrate and its manufacturing method and application. Background Technology
[0002] TGV substrates, or Through-Glass Via (TGV) substrates, are glass substrates with vertical electrical interconnects. They are used for miniaturization packaging in semiconductor and microelectronic device fields. Vertical electrical interconnects are achieved through metal-filled vias. Typically, borosilicate glass or quartz glass is used as the substrate, and the process involves laser-induced via etching, seed layer sputtering, via electroplating filling, bumping, and redistribution layer (RDL) processes. For various applications in advanced packaging, tens of thousands of TGVs are usually required per wafer, and these are metallized to ensure the required conductivity.
[0003] Compared to the silicon substrate used in Through-Silica Via (TSV) technology, the dielectric constant of glass is only about 1 / 3 that of silicon, and its loss factor is 2-3 orders of magnitude lower than that of silicon. This can greatly reduce substrate loss and parasitic effects, ensuring the integrity of transmitted signals. Furthermore, TGV substrates do not require complex insulating layer deposition processes, and large-size ultra-thin panel glass is readily available, greatly reducing manufacturing costs. Therefore, TGV substrates have unique advantages in fields such as RF chips, high-end MEMS sensors, and high-density system integration, making them one of the preferred choices for next-generation high-frequency chip 3D packaging.
[0004] Currently, the industry generally uses borosilicate glass and quartz glass as the glass materials for TGV substrates. Quartz glass, due to its extremely high cost and its ultra-low coefficient of thermal expansion that is incompatible with chip materials, is difficult to expand its application in chip packaging. Borosilicate glass, on the other hand, is prone to warping, cracking, and fragmentation in actual TGV processes and packaging verification due to insufficient strength. To reduce the impact on end-applications, it is necessary to develop a microcrystalline glass with better mechanical strength to provide a better glass material for TGV technology. Summary of the Invention
[0005] The purpose of this application is to provide a microcrystalline glass and its preparation method, a TGV substrate and its manufacturing method and application, to obtain a glass material with high mechanical strength and low dielectric loss, which can achieve high-density through-holes in the TGV process, and the through-holes can achieve high perpendicularity. The specific technical solution is as follows:
[0006] A first aspect of this application provides a microcrystalline glass, which, by weight percentage, comprises:
[0007] SiO2: 69wt%~75wt%, Al2O3: 5wt%~9wt%, P2O5: 1wt%~3wt%, ZrO2: 4wt%~7wt%, Na 2O+K2O: 0wt%~2wt%, Li2O: 9wt%~13wt%, CaO: 0.3wt%~1.3wt%, B2O3: 0wt%~2wt%,
[0008] Furthermore, SiO2+Al2O3≥75wt%, 0.12≤Li2O / SiO2≤0.18, 1.25≤Li2O / Al2O3≤2.
[0009] In one embodiment, the microcrystalline glass comprises:
[0010] SiO2: 70wt%~74wt%, Al2O3: 6wt%~8wt%, P2O5: 1.5wt%~2.75wt%, ZrO2: 4.5wt%~6.5wt%, N a2O+K2O: 0.5wt%~1.5wt%, Li2O: 10wt%~12wt%, CaO: 0.45wt%~1wt%, B2O3: 0.5wt%~1wt%.
[0011] In one implementation, 1.3 ≤ Li2O / Al2O3 ≤ 1.8.
[0012] In one embodiment, the microcrystalline glass comprises: Na₂O: 0.3wt%~0.8wt%, K₂O: 0.1wt%~0.4wt%;
[0013] Preferably, the microcrystalline glass comprises: Na2O: 0.4wt%~0.7wt%, K2O: 0.1wt%~0.35wt%.
[0014] In one embodiment, the microcrystalline glass has a dielectric constant of 5.48-5.83 and a dielectric loss of ≤0.0040 at a frequency of 5 GHz.
[0015] In one embodiment, the Young's modulus of the microcrystalline glass is ≥100 GPa, preferably 101 GPa-111 GPa.
[0016] In one embodiment, the microcrystalline glass has a Vickers hardness of 660 kgf / mm². 2 -680Kgf / mm 2 .
[0017] In one embodiment, the microcrystalline glass has a transmittance of ≥90.5% at a wavelength of 550nm when the thickness is 0.5mm.
[0018] In one embodiment, the crystalline phase of the microcrystalline glass comprises lithium disilicate and lithium feldspar.
[0019] The second aspect of this application provides a method for preparing the microcrystalline glass provided in the first aspect of this application, comprising the following steps:
[0020] Weigh and mix the raw materials to obtain a mixture;
[0021] The mixture is melted at 1500℃~1670℃, shaped, and annealed at 460℃~560℃ to obtain a glass matrix;
[0022] The glass substrate is subjected to crystallization heat treatment and then cooled to obtain the microcrystalline glass.
[0023] The crystallization heat treatment includes nucleation treatment and crystallization treatment. The temperature of the nucleation treatment is 540℃~570℃ and the time is 2h~8h. The temperature of the crystallization treatment is 660℃~760℃ and the time is 10min~4h.
[0024] The third aspect of this application provides a TGV substrate, which is made using the microcrystalline glass provided in the first aspect of this application.
[0025] In one embodiment, a through-hole is formed on the TGV substrate, and when the depth-to-diameter ratio of the through-hole is 10:1, the waist-to-diameter ratio of the through-hole is greater than 0.8.
[0026] Wherein, the depth-to-diameter ratio is the ratio of the depth of the through hole to the top diameter, and the waist-to-diameter ratio is the ratio of the waist diameter to the top diameter of the through hole.
[0027] The fourth aspect of this application provides a method for manufacturing a TGV substrate, comprising:
[0028] Microcrystalline glass provided by the first aspect of this application or microcrystalline glass prepared according to the preparation method provided by the second aspect of this application;
[0029] Laser-induced etching is performed on the microcrystalline glass to form through holes;
[0030] The through-holes are metallized to obtain the TGV substrate.
[0031] The fifth aspect of this application provides an application of the TGV substrate provided in the third aspect of this application or the TGV substrate prepared according to the manufacturing method provided in the fourth aspect of this application in electronic packaging.
[0032] In one embodiment, the electronic package is a radio frequency module package, a passive device package, a Mini-LED package, a Micro-LED package, a glass-based IC substrate package, a 2.5D package interposer, a 3D package interposer, an AI chip package, a CPU package, a GPU package, an ASIC package, a microfluidic device package, a consumer electronics package, or an automotive electronics package.
[0033] The beneficial effects of this application are:
[0034] This application provides a microcrystalline glass and its preparation method, a TGV substrate and its manufacturing method and application. The microcrystalline glass comprises, by weight percentage: SiO2: 69wt%~75wt%, Al2O3: 5wt%~9wt%, P2O5: 1wt%~3wt%, ZrO2: 4wt%~7wt%, Na2O+K2O: 0wt%~2wt%, Li2O: 9wt%~13wt%, CaO: 0.3wt%~1.3wt%, B2O3: 0wt%~2wt%, and SiO2+Al2O3≥75wt%, 0.12≤Li2O / SiO2≤0.18, 1.25≤Li2O / Al2O3≤2. By employing microcrystalline glass with oxide composition and content within the scope of this application, and by controlling the values of Li2O / SiO2 and Li2O / Al2O3 within the scope of this application, target crystals of lithium disilicate and lithium feldspar can be precipitated inside the microcrystalline glass. This results in rod-shaped interlacing of crystals within the microcrystalline glass, which is beneficial for resisting the generation and propagation of cracks during the TGV process. Furthermore, the microcrystalline glass of this application possesses good mechanical strength, which is beneficial for resisting warping and deformation in post-TGV processes. Simultaneously, the microcrystalline glass of this application exhibits good dielectric properties and high transmittance, meeting the requirements of TGV processes in the optical field. It provides glass raw materials with excellent mechanical properties for the TGV process, enabling the creation of high-density through-holes, blind holes, and blind slots. Through-holes can achieve high perpendicularity, with a waist-to-diameter ratio reaching 0.85. Attached Figure Description
[0035] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other embodiments can be obtained based on these accompanying drawings.
[0036] Figure 1 This is a process flow diagram of a TGV substrate according to one embodiment of the present application, including TGV via process and metallization process;
[0037] Figure 2 Photograph of a TGV sample with a diameter of 200 mm obtained in Example 6;
[0038] Figure 3 The image shows a TGV sample of glass-ceramic with dimensions of 50mm × 50mm × 0.6mm prepared in Example 6 under an AxioLab 5 microscope.
[0039] Figure 4 This is a photograph of the cross-section of the TGV microcrystalline glass sample with dimensions of 50mm × 50mm × 0.6mm prepared in Example 6 under an AxioLab 5 microscope. Detailed Implementation
[0040] The technical solutions of this application will be clearly and completely described below with reference to the embodiments and accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. All other embodiments obtained by those skilled in the art based on this application are within the scope of protection of this application.
[0041] The first aspect of this application provides a microcrystalline glass, which, by weight percentage, comprises: SiO2: 69wt%~75wt%, Al2O3: 5wt%~9wt%, P2O5: 1wt%~3wt%, ZrO2: 4wt%~7wt%, Na2O+K2O: 0wt%~2wt%, Li2O: 9wt%~13wt%, CaO: 0.3wt%~1.3wt%, B2O3: 0wt%~2wt%, and SiO2+Al2O3≥75wt%, 0.12≤Li2O / SiO2≤0.18, 1.25≤Li2O / Al2O3≤2.For example, in the microcrystalline glass, the SiO2 content, by mass percentage, can be 69wt%, 70wt%, 71wt%, 72wt%, 73wt%, 74wt%, 75wt%, or any range of two such values; the Al2O3 content can be 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, or any range of two such values; and the P2O5 content can be 1wt%, 1.25wt%, 1.5wt%, 1.75wt%, 2wt%, 2.25wt%, 2.5wt%, 2.75wt%, 3wt%, or any two such values. The numerical ranges are as follows: ZrO2 content can be 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, or any two of these values; Na2O+K2O content can be 0wt%, 0.3wt%, 0.5wt%, 0.8wt%, 1wt%, 1.3wt%, 1.5wt%, 1.8wt%, 2wt%, or any two of these values; Li2O content can be 9wt%, 9.5wt%, 10wt%, 10.5wt%, 11wt%, 11.5wt%, 1 The content can be 2wt%, 12.5wt%, 13wt%, or any two of these values; the CaO content can be 0.3wt%, 0.45wt%, 0.5wt%, 0.6wt%, 0.8wt%, 1wt%, 1.1wt%, 1.3wt%, or any two of these values; the B2O3 content can be 0wt%, 0.3wt%, 0.5wt%, 0.8wt%, 1wt%, 1.3wt%, 1.5wt%, 1.8wt%, 2wt%, or any two of these values; the calculated SiO2+Al2O3 content can be... The calculated Li2O / SiO2 content can be 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, or any two of these values; the calculated Li2O / Al2O3 content can be 1.25, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, or any two of these values.
[0042] In the composition of the microcrystalline glass of this application, SiO2 forms the glass network framework. When the SiO2 content exceeds 75 wt%, the high-temperature viscosity of the glass increases, making the melting and forming of the glass difficult and hindering mass production. In order to control the precipitation of the crystalline phases of lithium disilicate and lithite included in this application in the microcrystalline glass, the SiO2 content of this application is limited to 69 wt% to 75 wt%, preferably 70 wt% to 74 wt%.
[0043] Al2O3 can increase the Young's modulus of glass, which is beneficial to improving the glass's resistance to deformation. The microcrystalline glass of this application already contains a high content of SiO2. If the content of Al2O3 is too high, the glass will be difficult to melt. At the same time, in order to control the precipitation of the crystal phases of lithium disilicate and lithium feldspar included in this application in the microcrystalline glass, the Al2O3 content is limited to 5wt%~9wt%, preferably 6wt%~8wt%.
[0044] P2O5 can reduce the high-temperature viscosity of glass. At the same time, a small amount of P2O5 increases the connectivity of the glass network, which can improve the chemical stability and mechanical strength of the glass. In addition, P2O5 can induce phase separation and is a commonly used nucleating agent for lithium silicon glass. However, if the P2O5 content is too high, such as more than 3 wt%, it will affect the chemical stability and glass formation stability of the glass and easily lead to crystallization during the glass forming process. Therefore, this application limits the P2O5 content to 1 wt% to 3 wt%, preferably 1.5 wt% to 2.75 wt%.
[0045] ZrO2 can improve the wear resistance and mechanical strength of glass, and can also be used as a nucleating agent for the microcrystalline glass of this application to promote the precipitation of the characteristic crystalline phase of the microcrystalline glass of this application. However, ZrO2 has a high melting temperature. If the content is too high, the high viscosity at high temperature will make it difficult to melt the glass. Therefore, this application limits the ZrO2 content to 4wt%~7wt%, preferably 4.5wt%~6.5wt%.
[0046] Li2O can reduce the high-temperature viscosity of glass and help the glass melt. At the same time, Li2O is the main component of the microcrystalline glass in this application and has a high content. In order to obtain microcrystalline glass with high crystallinity of target crystal phase, this application limits the Li2O / SiO2 ratio to 0.12~0.18 and the Li2O content to 9wt%~13wt%, preferably 10wt%~12wt%.
[0047] Na2O+K2O: can reduce glass melting temperature and high-temperature viscosity. However, if the content is too high, it will lead to an increase in dielectric constant and dielectric loss. Therefore, the content of Na2O+K2O in this application is limited to 0wt%~2wt%, preferably 0.5wt%~1.5wt%.
[0048] B2O3 is a glass network forming material that can improve the meltability and devitrification resistance of glass. In this application, due to the high content of SiO2+Al2O3, the high viscosity at high temperature is relatively large, so a small amount of B2O3 can be added as a flux. However, in order not to affect the overall crystallization characteristics and mechanical properties of the glass, the B2O3 content is low, limited to 0wt%~2wt%, preferably 0.5wt%~1wt%.
[0049] CaO can reduce the high-temperature viscosity of glass, which is beneficial to glass melting, clarification and homogenization. In order to achieve highly crystalline microcrystalline glass, the composition of amorphous components needs to be limited. Therefore, this application limits the CaO content to 0.3wt%~1.3wt%, preferably 0.45wt%~1wt%.
[0050] To achieve the desired crystal precipitation of lithium disilicate (Li2Si2O5) and petrified feldspar (LiAlSi4O5) in the microcrystalline glass of this application... 10 The SiO2+Al2O3 ≥ 75wt%, 0.12 ≤ Li2O / SiO2 ≤ 0.18, and 1.25 ≤ Li2O / Al2O3 ≤ 2 are controlled.
[0051] By employing microcrystalline glass with oxide composition and content within the scope of this application, and by controlling the values of Li2O / SiO2 and Li2O / Al2O3 within the scope of this application, target crystals of lithium disilicate and lithium feldspar can be precipitated inside the microcrystalline glass. This results in rod-shaped interlacing of crystals within the microcrystalline glass, which is beneficial for resisting the generation and propagation of cracks during the TGV process. Furthermore, the microcrystalline glass of this application possesses excellent mechanical strength, which is beneficial for resisting warping and deformation in post-TGV processes. Simultaneously, the microcrystalline glass of this application exhibits good dielectric properties and high transmittance, meeting the requirements of TGV processes in the optical field. It can provide glass raw materials with excellent mechanical properties for TGV substrates and their applications, enabling the production of high-density through-holes, blind vias, and blind grooves, with through-holes achieving high perpendicularity.
[0052] In one embodiment, the microcrystalline glass comprises: SiO2: 70wt%~74wt%, Al2O3: 6wt%~8wt%, P2O5: 1.5wt%~2.75wt%, ZrO2: 4.5wt%~6.5wt%, Na2O+K2O: 0.5wt%~1.5wt%, Li2O: 10wt%~12wt%, CaO: 0.45wt%~1wt%, and B2O3: 0.5wt%~1wt%. Adjusting the oxide content within this range is beneficial for further improving the mechanical strength of the microcrystalline glass.
[0053] In one embodiment, 1.3 ≤ Li₂O / Al₂O₃ ≤ 1.8. Adjusting the Li₂O / Al₂O₃ ratio within this range enables the glass-ceramic to possess higher mechanical strength and lower dielectric loss.
[0054] In one embodiment, the glass-ceramic comprises: Na₂O: 0.3wt%~0.8wt%, K₂O: 0.1wt%~0.4wt%; preferably, the glass-ceramic comprises: Na₂O: 0.4wt%~0.7wt%, K₂O: 0.1wt%~0.35wt%. For example, in the glass-ceramic, the Na₂O content, by mass percentage, can be 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, or a range of any two of these values; the K₂O content can be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, or a range of any two of these values. Controlling the Na₂O and K₂O content within this range is beneficial for further reducing the dielectric loss of the glass-ceramic.
[0055] In one embodiment, the dielectric constant of the microcrystalline glass at a frequency of 5 GHz is 5.48-5.83, and the dielectric loss is ≤0.0040. For example, the dielectric constant of the microcrystalline glass at a frequency of 5 GHz can be 5.48, 5.5, 5.52, 5.53, 5.55, 5.57, 5.58, 5.6, 5.61, 5.63, 5.65, 5.68, 5.7, 5.72, 5.75, 5.77, 5.8, 5.83, or a range of any two values therein, and the dielectric loss can be 0.001, 0.0015, 0.002, 0.0025, 0.003, 0.0035, 0.004, or a range of any two values therein. The dielectric constant and dielectric loss being within the above ranges indicate that the microcrystalline glass of this application possesses good dielectric properties.
[0056] In one embodiment, the Young's modulus of the microcrystalline glass is ≥100 GPa, preferably 101 GPa-111 GPa. For example, the Young's modulus of the microcrystalline glass can be 100 GPa, 101 GPa, 102 GPa, 103 GPa, 104 GPa, 105 GPa, 106 GPa, 107 GPa, 108 GPa, 109 GPa, 110 GPa, 111 GPa, or a range consisting of any two of these values. A Young's modulus within the above range indicates that the microcrystalline glass of this application possesses good mechanical properties.
[0057] In one embodiment, the microcrystalline glass has a Vickers hardness of 660 kgf / mm². 2 -680Kgf / mm 2 For example, the Vickers hardness of the microcrystalline glass can be 660 kgf / mm. 2 663Kgf / mm 2 665Kgf / mm 2668Kgf / mm 2 670Kgf / mm 2 673Kgf / mm 2 675Kgf / mm 2 678Kgf / mm 2 680Kgf / mm 2 Or it can be a range consisting of any two of these values. A Vickers hardness within the above range indicates that the microcrystalline glass of this application possesses good mechanical properties.
[0058] In one embodiment, the microcrystalline glass, with a thickness of 0.5 mm, has a transmittance of ≥90.5% at a wavelength of 550 nm, preferably 90.5%-91.5%. For example, the transmittance of the microcrystalline glass with a thickness of 0.5 mm at a wavelength of 550 nm can be 90.5%, 91%, 91.5%, or a range of any two of these values. The fact that the transmittance at a wavelength of 550 nm at a thickness of 0.5 mm meets the above range indicates that the microcrystalline glass of this application has high transmittance, which can meet the requirements of TGV processes in the optical field.
[0059] In one embodiment, the density of the microcrystalline glass is 2.48 g / cm³. 3 -2.53g / cm 3 For example, the density of the microcrystalline glass can be 2.48 g / cm³. 3 2.49 g / cm 3 2.50g / cm 3 2.51g / cm 3 2.52g / cm 3 2.53g / cm 3 Or it can be a range consisting of any two of these values.
[0060] In one embodiment, the crystalline phase of the microcrystalline glass comprises lithium disilicate and lithium feldspar.
[0061] The second aspect of this application provides a method for preparing the microcrystalline glass provided in the first aspect of this application, comprising the following steps:
[0062] Weigh the raw materials and mix them to obtain a mixture.
[0063] The mixture is melted at 1500℃~1670℃, shaped, and annealed at 460℃~560℃ to obtain a glass matrix;
[0064] The glass substrate is subjected to crystallization heat treatment and then cooled to obtain the microcrystalline glass.
[0065] The crystallization heat treatment includes nucleation treatment and crystallization treatment. The temperature of the nucleation treatment is 540℃~570℃ and the time is 2h~8h. The temperature of the crystallization treatment is 660℃~760℃ and the time is 10min~4h.
[0066] This application does not have any particular limitation on the raw materials mentioned, as long as they can achieve the purpose of this application; in one embodiment, the raw materials may include, but are not limited to, silica sand, alumina or aluminum hydroxide, aluminum phosphate, lithium carbonate, zirconium oxide, sodium carbonate, potassium carbonate, calcium carbonate, boric acid, etc.
[0067] A third aspect of this application provides a TGV substrate made from the microcrystalline glass provided in the first aspect of this application. The TGV substrate described in this application enables high-density vertical electrical interconnect packaging.
[0068] In one embodiment, a through-hole is formed on the TGV substrate, and when the depth-to-diameter ratio of the through-hole is 10:1, the waist-to-diameter ratio of the through-hole is greater than 0.8, preferably 0.81-0.85;
[0069] Wherein, the depth-to-diameter ratio is the ratio of the depth of the through hole to the top diameter, and the waist-to-diameter ratio is the ratio of the waist diameter to the top diameter of the through hole.
[0070] The fourth aspect of this application provides a method for manufacturing a TGV substrate, comprising:
[0071] Microcrystalline glass provided by the first aspect of this application or microcrystalline glass prepared according to the preparation method provided by the second aspect of this application;
[0072] Laser-induced etching is performed on the microcrystalline glass to form through holes;
[0073] The through-holes are metallized to obtain the TGV substrate.
[0074] In one implementation scheme, such as Figure 1As shown, the TGV substrate can use the microcrystalline glass of this application as the glass material, which is laser-induced and etched into vias, and then the vias are metallized. The metallization process includes seed layer sputtering, electroplating filling, bumping, and RDL treatment. This application does not have any particular limitations on each process step, and conventional processing techniques in the art can be used, as long as the purpose of this application can be achieved. For example, the laser induction can be performed using a femtosecond laser to treat the area where vias need to be formed, and the spot size can be 0.5μm-1.5μm; the via etching can be performed by etching the laser-induced glass with acid or alkali to form vias. For example, alkaline etching can be used. Specifically, the laser-induced glass material is immersed in a 20wt%-30wt% NaOH solution; after seed layer sputtering, a seed layer is deposited on the inner wall of the via; electroplating is used for metal filling; and then bumping and RDL treatment are performed.
[0075] The fifth aspect of this application provides an application of the TGV substrate provided in the third aspect of this application or the TGV substrate prepared according to the manufacturing method provided in the fourth aspect of this application in electronic packaging.
[0076] In one embodiment, the electronic package is a radio frequency module package, a passive device package, a Mini-LED package, a Micro-LED package, a glass-based IC substrate package, a 2.5D package interposer, a 3D package interposer, an AI chip package, a CPU package, a GPU package, an ASIC package, a microfluidic device package, a consumer electronics package, or an automotive electronics package, etc.
[0077] Based on the superior performance of the microcrystalline glass of this application, the TGV substrate of this application can be widely used in the field of electronic packaging, including but not limited to RF module packaging, passive device packaging, Mini-LED / Micro-LED packaging, glass-based IC substrate, 2.5D / 3D packaging interposer, AI chip and various processor chip packaging, microfluidic device packaging, and consumer electronics and automotive electronics product packaging, etc.
[0078] Example
[0079] The embodiments and comparative examples provided below illustrate the implementation of this application in more detail. Various tests and evaluations were conducted according to the methods described below. Furthermore, unless otherwise specified, "parts" and "%" are quality standards.
[0080] Test methods and equipment:
[0081] Young's modulus test:
[0082] Young's modulus is a physical quantity that measures the elastic stiffness of a material, that is, the ratio of stress to strain. The test method refers to the national standard GB / T 7962.6-2010- "Test Methods for Colorless Optical Glass Part 6: Young's Modulus, Shear Modulus and Poisson's Ratio", and the Young's modulus of microcrystalline glass is tested using the ultrasonic echo material testing system (UMS-200).
[0083] Vickers hardness test:
[0084] The Vickers hardness of the microcrystalline glass was tested using a micro Vickers hardness tester (model: VTA402A, manufacturer: Beijing Woway Technology Co., Ltd.).
[0085] Crystal type analysis:
[0086] The crystal types of glass-ceramics were analyzed using an X-ray diffractometer (XRD, model: XRD-6100, manufacturer: Shimadzu Instruments).
[0087] Crystal micromorphology observation:
[0088] The microstructure of the glass-ceramic crystals was observed using a high-resolution scanning electron microscope (model: Sigma 360, manufacturer: Zeiss).
[0089] Transmittance test:
[0090] The transmittance of the microcrystalline glass at a wavelength of 550 nm with a thickness of 0.5 mm was tested using a UV-Vis spectrophotometer (model: UV-2600, manufacturer: Shimadzu Instruments).
[0091] Dielectric constant and dielectric loss testing:
[0092] The dielectric constant and dielectric loss of the microcrystalline glass were obtained by using a discrete column dielectric resonator (SPDR) at a test frequency of 5 GHz.
[0093] Thermal expansion coefficient test:
[0094] Referring to the national standard GB / T 7962.16-2010- "Test Methods for Colorless Optical Glass - Part 16: Coefficient of Linear Expansion, Transition Temperature and Sag Temperature", the average linear thermal expansion coefficient is calculated by measuring the length change of the microcrystalline glass sample during the heating process. This application calculates the linear thermal expansion coefficient from 20℃ to 300℃.
[0095] Waist-to-diameter ratio test:
[0096] The TGV sample with a size of 50mm×50mm×0.6mm microcrystalline glass has a through-hole depth of approximately 0.6mm. The cross-sectional photographs of the TGV sample were tested and analyzed using an AxioLab5 microscope (ZEISS) to obtain the top diameter and waist diameter of the through-hole. The depth-to-diameter ratio of the TGV sample in each embodiment or comparative example is approximately 10:1, which is equal to the depth of the through-hole / the top diameter. The waist-to-diameter ratio of the TGV sample was calculated using the formula waist-to-diameter ratio = waist diameter / top diameter.
[0097] Example 1
[0098] The raw materials were prepared according to the proportions of each oxide in Table 1. The prepared raw materials were mixed to obtain a mixture. The mixture was melted at 1600℃, shaped, annealed at 510℃, and then subjected to nucleation and crystallization treatments (heating rate 10℃ / min). It was then naturally cooled to room temperature to obtain microcrystalline glass. The nucleation treatment temperature and time, and the crystallization treatment temperature and time are shown in Table 1.
[0099] Using this microcrystalline glass as the raw material, after cutting and polishing, a glass through-hole sample was obtained through laser induction and alkaline solution etching. The laser induction step is as follows: the polished glass substrate is treated with an ultrafast laser, the laser beam is shaped into a Bessel beam, and the spot size is 1.0 μm. The alkaline solution etching step is as follows: the glass substrate raw material after ultrafast laser treatment is immersed in a 25wt% NaOH solution for etching.
[0100] Examples 2 to 10
[0101] Except for adjusting the corresponding preparation parameters according to Table 1, everything else is the same as in Example 1. The photograph of the glass through-hole sample (200mm diameter glass wafer) prepared in Example 6 is shown below. Figure 2 As shown, an image of a TGV sample made of 50mm × 50mm × 0.6mm microcrystalline glass under an AxioLab 5 microscope (Zeiss ZEISS) is shown. Figure 3 As shown (scale bar 10μm), the hole roundness is relatively high. The cross-section of the TGV through-hole sample of the 50mm × 50mm × 0.6mm microcrystalline glass in this embodiment is shown in the image under an AxioLab 5 microscope. Figure 4 As shown (scale bar 50μm), the top diameter of the through hole is 62.393μm, the waist diameter is 51.594μm, and the depth of the through hole is 635.447μm. The calculated depth-to-diameter ratio is approximately 10:1, and the waist-to-diameter ratio = waist diameter / top diameter = 51.594μm / 62.393μm = 0.83.
[0102] Comparative Examples 1 to 5
[0103] Except for adjusting the corresponding preparation parameters according to Table 1, everything else is the same as in Example 1.
[0104] The relevant preparation parameters and performance test results of the microcrystalline glass in each embodiment or comparative example are shown in Table 1.
[0105] Table 1
[0106] The results of Examples 1-10 and Comparative Examples 1-5 show that by using the oxide composition of this application and adjusting the content ratios of Li2O / SiO2 and Li2O / Al2O3 within the range of this application, lithium disilicate (Li2Si2O5) and petalite (LiAlSi4O3) can be precipitated inside the glass-ceramic. 10 The internal crystals of the microcrystalline glass are arranged in a rod-like, interlocking pattern, which helps resist the generation and propagation of cracks during the TGV process. It significantly improves the Young's modulus and Vickers hardness of the microcrystalline glass, enhancing its strength and giving it excellent mechanical properties, thus resisting warping and deformation during the TGV process. The dielectric constant of the microcrystalline glass in Examples 1-10 is 5.48-5.68, and the dielectric loss is ≤0.0039, both low, indicating good dielectric properties. The transmittance of the microcrystalline glass in Examples 1-10 at a thickness of 0.5 mm and a wavelength of 550 nm is >90.5%, demonstrating high transmittance. Furthermore, using the microcrystalline glass provided in this application, high-density through-holes can be obtained, achieving high perpendicularity and a waist-to-diameter ratio of 0.81-0.85. When used to prepare TGV substrates, this results in TGV substrates with excellent dielectric properties.
[0107] It should be noted that, in this document, the terms “comprising,” “including,” or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, or article that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, or article.
[0108] The various embodiments in this specification are described in a related manner. The same or similar parts between the various embodiments can be referred to each other. Each embodiment focuses on describing the differences from other embodiments.
[0109] The above description is only a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the scope of protection of this application.
Claims
1. A microcrystalline glass, characterized in that, The microcrystalline glass comprises, by weight percentage: SiO2: 69wt%~75wt%, Al2O3: 5wt%~9wt%, P2O5: 1wt%~3wt%, ZrO2: 4wt%~7wt%, Na 2O+K2O: 0wt%~2wt%, Li2O: 9wt%~13wt%, CaO: 0.3wt%~1.3wt%, B2O3: 0wt%~2wt%, Furthermore, SiO2+Al2O3≥75wt%, 0.12≤Li2O / SiO2≤0.18, 1.25≤Li2O / Al2O3≤2.
2. The microcrystalline glass according to claim 1, characterized in that, The microcrystalline glass comprises: SiO2: 70wt%~74wt%, Al2O3: 6wt%~8wt%, P2O5: 1.5wt%~2.75wt%, ZrO2: 4.5wt%~6.5wt%, N a2O+K2O: 0.5wt%~1.5wt%, Li2O: 10wt%~12wt%, CaO: 0.45wt%~1wt%, B2O3: 0.5wt%~1wt%.
3. The microcrystalline glass according to claim 1, characterized in that, 1.3≤Li2O / Al2O3≤1.
8.
4. The microcrystalline glass according to claim 1, characterized in that, The microcrystalline glass comprises: Na₂O: 0.3wt%~0.8wt%, K₂O: 0.1wt%~0.4wt%; Preferably, the microcrystalline glass comprises: Na2O: 0.4wt%~0.7wt%, K2O: 0.1wt%~0.35wt%.
5. The microcrystalline glass according to any one of claims 1-4, characterized in that, The dielectric constant of the microcrystalline glass at a frequency of 5 GHz is 5.48-5.83, and the dielectric loss is ≤0.0040.
6. The microcrystalline glass according to any one of claims 1-4, characterized in that, The Young's modulus of the microcrystalline glass is ≥100 GPa, preferably 101 GPa-111 GPa.
7. The microcrystalline glass according to any one of claims 1-4, characterized in that, The Vickers hardness of the microcrystalline glass is 660 kgf / mm². 2 -680Kgf / mm 2 .
8. The microcrystalline glass according to any one of claims 1-4, characterized in that, The microcrystalline glass has a transmittance of ≥90.5% at a wavelength of 550nm when the thickness is 0.5mm.
9. The microcrystalline glass according to any one of claims 1-4, characterized in that, The crystalline phases of the microcrystalline glass include lithium disilicate and petalite.
10. A method for preparing a microcrystalline glass according to any one of claims 1-9, characterized in that, Includes the following steps: Weigh and mix the raw materials to obtain a mixture; The mixture is melted at 1500℃~1670℃, shaped, and annealed at 460℃~560℃ to obtain a glass matrix; The glass substrate is subjected to crystallization heat treatment and then cooled to obtain the microcrystalline glass. The crystallization heat treatment includes nucleation treatment and crystallization treatment. The temperature of the nucleation treatment is 540℃~570℃ and the time is 2h~8h. The temperature of the crystallization treatment is 660℃~760℃ and the time is 10min~4h.
11. A TGV substrate, characterized in that, It is prepared using the microcrystalline glass according to any one of claims 1-9.
12. The TGV substrate according to claim 11, characterized in that, A through-hole is formed on the TGV substrate. When the depth-to-diameter ratio of the through-hole is 10:1, the waist-to-diameter ratio of the through-hole is greater than 0.
8. Wherein, the depth-to-diameter ratio is the ratio of the depth of the through hole to the top diameter, and the waist-to-diameter ratio is the ratio of the waist diameter to the top diameter of the through hole.
13. A method for manufacturing a TGV substrate, characterized in that, include: The microcrystalline glass according to any one of claims 1-9 or the microcrystalline glass prepared by the preparation method according to claim 10; Laser-induced etching is performed on the microcrystalline glass to form through holes; The through-holes are metallized to obtain the TGV substrate.
14. The application of a TGV substrate according to claim 11 or 12 or a TGV substrate manufactured by the manufacturing method according to claim 13 in electronic packaging.
15. The application according to claim 14, characterized in that, The electronic packaging includes radio frequency module packaging, passive device packaging, Mini-LED packaging, Micro-LED packaging, glass-based IC substrate packaging, 2.5D packaging interposer, 3D packaging interposer, AI chip packaging, CPU packaging, GPU packaging, ASIC packaging, microfluidic device packaging, consumer electronics packaging, or automotive electronics packaging.